2012
DOI: 10.1124/jpet.112.198176
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Ca2+–Induced Apoptosis in Rat Cardiomyocytes via Mitochondrial NO-cGMP-Protein Kinase G Pathway

Abstract: Previously, we showed that in adult rat cardiomyocytes, nitric oxide (NO) donors stimulate mitochondrial cGMP production, followed by cytochrome c release, independently of the mitochondrial permeable transition pore. We investigated whether mitochondrial cGMP-induced cytochrome c release from cardiac mitochondria is Ca 21 -sensitive. Mitochondria and primary cultured cardiomyocytes were prepared from left ventricles of male Wistar rats. The cytosolic Ca 21 concentration was adjusted with Ca 21 -EGTA buffers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…All these data indicate that the elements of Ca 2+ ‐dependent mtNOS/guanylate cyclase (GC)/PKG signaling system (mtNOS‐SS) may operate in mitochondria. However, according to the results presented by Seya and coauthors , S ‐nitrosoacetylpenacillamine (SNAP) or 8‐Bromo‐cGMP stimulated calcium‐dependent CytC release and apoptosis, while the inhibitors of NOS, GC, and PKG prevented these effects. These results contradict the generally admitted prosurvival action of cytosolic NOS/GC/PKG1 signaling system involved in the prevention of mPTP opening and cell death .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…All these data indicate that the elements of Ca 2+ ‐dependent mtNOS/guanylate cyclase (GC)/PKG signaling system (mtNOS‐SS) may operate in mitochondria. However, according to the results presented by Seya and coauthors , S ‐nitrosoacetylpenacillamine (SNAP) or 8‐Bromo‐cGMP stimulated calcium‐dependent CytC release and apoptosis, while the inhibitors of NOS, GC, and PKG prevented these effects. These results contradict the generally admitted prosurvival action of cytosolic NOS/GC/PKG1 signaling system involved in the prevention of mPTP opening and cell death .…”
Section: Introductionmentioning
confidence: 97%
“…However, potential intramitochondrial mechanisms of protection may also include some signaling chains involved in calcium and NO interplay. Recently, Seya and coauthors discovered that cardiac mitochondrial protein fraction possesses protein kinase G (PKG) activity and provides cGMP synthesis triggered by NO donors . Besides, the hydrolysis of cGMP by mitochondrial cyclic nucleotide phosphodiesterase PDE2A was demonstrated in brain and liver mitochondria in independent experiments .…”
Section: Introductionmentioning
confidence: 99%
“…All these data indicate that the elements Ca 2+ -dependent mtNOS/ GC/PKG-signaling system (mtNOS-SS) may operate in mitochondria. However, according to 4 the results presented by Seya and coauthors [23], SNAP or 8-Bromo-cGMP induced calciumdependent CytC release and apoptosis, while the inhibitors of NOS, GC, and PKG prevented these effects. These results contradict to the generally admitted pro-survival action of cytosolic NOS/GC/PKG1-SS directed at the prevention of MPTP opening and cell death [26][27][28][29].…”
Section: Introductionmentioning
confidence: 92%
“…However, potential intramitochondrial mechanisms of protection may also include some signaling chains involved in calcium and NO interplay. Recently Seya and coauthors discovered that cardiac mitochondrial protein fraction possesses PKG activity [23] and provides cGMP synthesis triggered by NO donors [24]. Besides, the hydrolysis of cGMP by mitochondrial cyclic nucleotide phosphodiesterase PDE2A was demonstrated in brain and liver mitochondria in independent experiments [25].…”
Section: Introductionmentioning
confidence: 99%
“…PKG1α arbitrates the down-stream effects that are involved in keeping the contractile force of cardiomyocytes and phosphorylates serine and threonine residues on numerous cytosolic proteins [13]. Seya et al found that the NO-cGMP-PKG pathway might play a role in ischemic pre-conditioning and antioxidant cardiac protection via cardiac mitochondria [14], even though the precise mechanism remains to be discovered. PDE5 inhibitors, such as sildenafil (SIL), prolong the effect of NO, a potent vasodilator, and cGMP, causing increased vasodilation and smooth muscle tone regulation [15].…”
Section: Introductionmentioning
confidence: 99%